Analisis Peningkatan Kualitas Guru pada UPT (Unit Pelayanan Terpadu) SMP Negeri 7 Medan - Indri Inayati; Isnaini Isnaini; Nina Siti Salmaniah Siregar (Mahesa Research Center, 2023)
The purpose of this study is to examine the analysis of improving teacher quality, the Synoxys of Teacher Quality at UPT (Integrated Service Unit), and Barriers to Improving Teacher Quality at UPT (Integrated Service Unit) SMP Negeri 7 Medan. The method used is descriptive quantitative with data instruments, study observation and documentation as well as interviews. The results of the study found that professional improvement in teacher quality in terms of professional knowledge and skills indicators that school principals and teachers improve teacher professionalism and create morale as well as human resources. The teacher's knowledge shows quality skills and skills. It is shown by the teacher's working spirit which is quite good with the existence of aspects that can trigger the emergence of enthusiasm for work. For this reason, enthusiasm from all teachers is needed in providing support and appreciating all activities given to teachers so that they are able to create a good quality teacher. The inhibiting factors for improving teacher quality are the low and lack of support from school principals for teacher quality improvement programs for teacher competence and the lack of support from school principals for teacher quality improvement programs.